Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $N(t)$ be a non-homogeneous Poisson process with rate function $\lambda(r),r\geq 0$. I have to find joint density function of arrival times $T_1$ and $T_2-T_1$ and to show that they are dependent. This is not a homework. Firstly I tried to calculate joint cdf and got $P(T_1\leq x,T_2-T_1\leq y)=$ $(1-e^{-\int^x_0 \lambda(r)dr})(1-e^{-\int^{x+y}_x \lambda(r)dr})$, I am not sure whether this is correct. Then I tried to find separate probabilities, $P(T_1\leq x)=P(N(x)>1)=$ $1-e^{-\int^x_0 \lambda(r)dr}$ and $P(T_2\leq y+T_1)=P(N(y+T_1)>2)=$ $1-e^{\int^{y+T_1}_0 \lambda(r)}$, the latter does not seem very "legal" so another idea was $P(T_2\leq y+T_1)=\int_0^{\infty} P(N(y+T_1)>2|T_1=s)P(N(s)=1)ds$. This question seems similar, but unfortunately did not really help me. Is my solution correct? The main problem is $T_2-T_1$ since it is non-homogeneous process, I am not sure how to deal with it.

share|cite|improve this question
You're fine on $T_1$. $P(T_2 - T_1 > y \vert T_1) = e^{-\int_{T_1}^{T_1 + y} \lambda(x) dx}$ – mike Apr 23 '12 at 19:00
up vote 3 down vote accepted

The answer is already on the other page, basically, but here we go.

For every $t\geqslant0$, let $\Lambda(t)=\int\limits_0^t\lambda(s)\mathrm ds$, hence $\frac{\mathrm d}{\mathrm dt}\Lambda(t)=\lambda(t)$.

  • The probability of the event $[T_1\geqslant t]$ that there is no arrival in $(0,t)$ is $\mathrm e^{-\Lambda(t)}$. Hence the density $f_1$ of the distribution of $T_1$ is minus the derivative of this, that is, $f_1(t)=\lambda(t)\mathrm e^{-\Lambda(t)}$.
  • Conditionally on $[T_1=t]$, the probability of the event $[T_2-T_1\geqslant s]$ that there is no arrival in $(t,t+s)$ is $\mathrm e^{\Lambda(t)-\Lambda(t+s)}$. Hence the conditional density $f_2(\ \mid t)$ of the distribution of $T_2-T_1$ is minus the derivative of this, that is, $f_2(s\mid t)=\lambda(t+s)\mathrm e^{\Lambda(t)-\Lambda(t+s)}$.

Putting everything together, one sees that the joint density $f$ of $(T_1,T_2-T_1)$ is given by, for every nonnegative $t$ and $s$, $$ f(t,s)=f_1(t)f_2(s\mid t)=\lambda(t)\lambda(t+s)\mathrm e^{-\Lambda(t+s)}. $$ Sanity check: In the homogenous case, $\lambda(t)=\lambda$ for every $t$ hence $\Lambda(t)=\lambda t$, $f_1(t)=\lambda\mathrm e^{-\lambda t}$ and $f(t,s)=\lambda^2\mathrm e^{-\lambda(t+s)}=f_1(t)f_1(s)$. Thus $T_1$ and $T_2-T_1$ are independent and exponentially distributed with parameter $\lambda$, as they should be.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.